2018
DOI: 10.1002/phar.2082
|View full text |Cite
|
Sign up to set email alerts
|

Hypotension Risk Based on Vasoactive Agent Discontinuation Order in Patients in the Recovery Phase of Septic Shock

Abstract: In patients recovering from septic shock treated with concomitant AVP and NE, no significant difference was noted in the incidence of hypotension based on discontinuation order of these agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 18 publications
0
57
0
1
Order By: Relevance
“…However, this 4‐hour requirement for maintenance of MAP is more likely to reflect the true transition point from early septic shock to the maintenance phase of septic shock than previously studied 1‐hour requirements for maintaining target MAP. More patients in the early concomitant vasopressin and norepinephrine group had vasopressin discontinued before norepinephrine in the resolving phase of septic shock that would not have any bearing on time to achieving and maintaining target MAP but may have affected duration of both vasopressors and intensive care unit length of stay . Finally, vasopressin was provided at an initial rate of 0.04 units/minute.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this 4‐hour requirement for maintenance of MAP is more likely to reflect the true transition point from early septic shock to the maintenance phase of septic shock than previously studied 1‐hour requirements for maintaining target MAP. More patients in the early concomitant vasopressin and norepinephrine group had vasopressin discontinued before norepinephrine in the resolving phase of septic shock that would not have any bearing on time to achieving and maintaining target MAP but may have affected duration of both vasopressors and intensive care unit length of stay . Finally, vasopressin was provided at an initial rate of 0.04 units/minute.…”
Section: Discussionmentioning
confidence: 99%
“…More patients in the early concomitant vasopressin and norepinephrine group had vasopressin discontinued before norepinephrine in the resolving phase of septic shock that would not have any bearing on time to achieving and maintaining target MAP but may have affected duration of both vasopressors and intensive care unit length of stay. [24][25] Finally, vasopressin was provided at an initial rate of 0.04 units/minute. The most recent iteration of the Surviving Sepsis Campaign guidelines recommends an initial rate of 0.03 units/minute.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated a higher incidence of hypotension after vasopressin discontinuation compared with NE discontinuation. [29][30][31][32][33] Patient demographics, vasopressor utilization, and clinical outcomes were similar to the overall cohort (Tables S1 and S2, Supporting Information).…”
Section: Discussionmentioning
confidence: 71%
“…In the recovery stage of shock, the discontinuation order of vasoactive medications could affect the risk for subsequent hypotension, and a number of studies have evaluated the discontinuation sequence of AVP and NE. In the largest study, which included only patients with septic shock, no difference was observed in the incidence of clinically significant hypotension whether AVP or NE was discontinued first (AVP discontinued first 55% vs NE discontinued first 50%; risk difference 5.1%, 95% confidence interval −4.1 to 14.2%, p=0.28) . However, in a multivariable Cox proportional hazards model, having AVP discontinued first was independently associated with an increased risk of hypotension.…”
Section: Strategies To Minimize Adr Risk For Both Agentsmentioning
confidence: 92%
“…In the largest study, which included only patients with septic shock, no difference was observed in the incidence of clinically significant hypotension whether AVP or NE was discontinued first (AVP discontinued first 55% vs NE discontinued first 50%; risk difference 5.1%, 95% confidence interval À4.1 to 14.2%, p=0.28). 55 However, in a multivariable Cox proportional hazards model, having AVP discontinued first was independently associated with an increased risk of hypotension. Because this difference in hypotension risk did not impact downstream clinical outcomes (such as alive intensive care unit [ICU]-free days or mortality), further studies are needed to inform clinical practice with an AVP and NE discontinuation sequence.…”
Section: Strategies To Minimize Adr Risk For Both Agentsmentioning
confidence: 95%